Frowning and Jaw Clenching Muscle Activity Reflects the Perception of Effort During Incremental Workload Cycling. - Ding-Hau Huang; Shih-Wei Chou; Yi-Lang Chen; Wen-Ko Chiou (Journal of Sports Science & Medicine, 2014)
The present study aimed to investigate whether facial electromyography (EMG) recordings reflect the perception of effort and primary active lower limb muscle activity during incremental workload cycling. The effects of exercise intensity on EMG activity of the corrugator supercilii (CS), masseter and vastus lateralis (VL) muscles, heart rate (HR) and the rating of perceived exertion (RPE) were investigated, and the correlations among these parameters were determined. Eighteen males and 15 females performed continuous incremental workload cycling exercise until exhaustion. CS, masseter and VL muscle activities were continuously recorded using EMG during exercise. HR was also continuously monitored during the test. During the final 30 s of each stage of cycle ergometer exercise, participants were asked to report their feeling of exertion on the adult OMNI- Cycle RPE. HR and EMG activity of the facial muscles and the primary active lower limb muscle were strongly correlated with RPE; they increased with power output. Furthermore, facial muscle activity increased significantly during high-intensity exercise. Masseter muscle activity was strongly and positively correlated with HR, RPE and VL activity. The present investigation supports the view that facial EMG activity reflects the perception of effort. The jaw clenching facial expression can be considered an important factor for improving the reporting of perceived effort during high-intensity exercise in males and females.